A59 FACTORS ASSOCIATED WITH ANXIETY ABOUT COLONOSCOPY: THE PREPARATION, THE PROCEDURE, AND THE ANTICIPATED FINDINGS. (1st March 2018) - Walker, J R; Shafer, L; Yang, V; Singh, A; Waldman, C; Michaud, V; Bernstein, C N; Park, J; Hathout, L; Sisler, J; Restall, G; Wittmeier, K; et al.
Abstract: Background: Previous research has assessed anxiety related to colonoscopy but has not specifically considered anxiety related to different aspects of the situation – bowel preparation, the procedure itself, and the anticipated findings. A better understanding of anxiety related to the various aspects of colonoscopy may help guide the development of resources or interventions to lessen colonoscopy-related anxiety. Aims: We aimed to assess anxiety immediately before a colonoscopy and evaluate variables associated with anxiety about different aspects of the procedure. Methods: A self-administered anonymous survey was distributed between August 2015 to June 2016 to patients immediately prior to their outpatient colonoscopy in Winnipeg's 6 hospitals and 2 ambulatory care centers. Anxiety was assessed with a visual analogue scale in which respondents indicated their anxiety about each of bowel preparation, the procedure and the findings on a 0 to 100 scale. A score of 70 or more was considered a high level of anxiety. Multivariate logistic regression analysis determined predictors of high anxiety. Results: Of the 1336 respondents (52% females, median age 57 years), 18% reported high anxiety about the bowel preparation, 29% about the procedure, and 28% about the findings of the procedure. Predictors of high anxiety about bowel preparation were: female gender (OR 2.90; 95% CI: 1.97–4.25), finding bowel prep information confusing (OR 3.29; 95% CI: 1.64–6.63), unfinished laxative intake (OR 1.71; 95% CI: 1.05–2.80), and high anxiety about the procedure itself (OR 3.06; 95% CI: 2.09–4.49). Predictors of high anxiety about the procedure were: female gender (OR 1.41; 95% CI: 1.02–1.94), high anxiety about bowel prep (OR 3.04; 95% CI: 2.07–4.47), and high anxiety about the findings (OR 4.58; 95% CI: 3.30–6.35), while lower anxiety was seen in those with more than one previous colonoscopy (OR 0.38; 95% CI: 0.24–0.58) and coming direct to scope (OR 0.71; 95% CI: 0.51–0.99). Predictors of high anxiety about the findings were polyp/cancer surveillance (OR 1.98; 95% CI: 1.18–3.30) or symptom investigation (OR 2.02; 95% CI: 1.36–3.00) as reasons for the procedure and anxiety about the procedure (OR 4.51; 95% CI: 3.26–6.24). There was no association between anxiety and educational attainment or the use of the split dose preparation for any of the aspects of the procedure. Conclusions: Fewer people had high anxiety about preparation than about the procedure and findings of the procedure. There are unique predictors of anxiety each of these factors. Higher quality information about preparation, the colonoscopy itself, and findings of the colonoscopy may help to reduce anxiety for some patients. Funding Agencies: Research Manitoba